2014
DOI: 10.1111/wej.12080
|View full text |Cite
|
Sign up to set email alerts
|

Contamination by organochlorine pesticides in the aquifer of the Ring of Cenotes in Yucatán, México

Abstract: Banned or restricted organochlorine pesticides in many countries worldwide are still in use in developing countries for agricultural and livestock activities, as well as for vector control in public health campaigns. The present study was conducted to map estimated concentrations of organochlorine pesticides in a karstic region in the Yucatan Peninsula, Mexico, known as ‘Ring of Cenotes’. Water samples from 20 sinkholes (‘cenotes’) were collected during the dry and rainy seasons in 2010–11, analysed by gas chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…Cenotes are seriously contaminated (Metcalfe et al 2011, Polanco-Rodríguez et al 2015, but our results indicate that the local people perceive contamination in a different way from scientific understanding. The linguistic classification of water (Table 4) reflects local knowledge, and the terms for different perceptions of "water" are helpful to deepen the analysis of how to improve water management to go from an undesirable to a desirable state.…”
Section: Discussion: a Biocultural Approach To Cenote Conservationcontrasting
confidence: 54%
See 2 more Smart Citations
“…Cenotes are seriously contaminated (Metcalfe et al 2011, Polanco-Rodríguez et al 2015, but our results indicate that the local people perceive contamination in a different way from scientific understanding. The linguistic classification of water (Table 4) reflects local knowledge, and the terms for different perceptions of "water" are helpful to deepen the analysis of how to improve water management to go from an undesirable to a desirable state.…”
Section: Discussion: a Biocultural Approach To Cenote Conservationcontrasting
confidence: 54%
“…For example, the Reserve was so designated because of the quality of water. However, some cenotes in the Reserve have been reportedly contaminated with pesticides (Polanco-Rodríguez et al 2015). Toxic contamination was not reflected in the understanding of participants regarding water quality, and pesticides were not mentioned as a potential factor affecting groundwater, even though in five of the cenotes explored, pesticide bottles were found.…”
Section: Present-day Uses Of Cenotesmentioning
confidence: 96%
See 1 more Smart Citation
“…The average dry season (March‐May) concentrations of p , p ´‐DDT, p , p ´‐DDE, and p , p ´‐DDD were 0.19 ppb, 0.41 ppb, and 0.90 ppb, respectively. Researchers (Polanco Rodríguez et al ) also reported the presence of organochlorine pesticides in water from the “cenotes” ring in Yucatan during rainy and dry seasons, although they reported higher concentrations. They reported p , p ´‐DDT concentration values of 16 ppb in the rainy season and 32 ppb in the dry season.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main problems generated by the uncontrolled use of organochloride pesticides is the pollution of aquatic environments through pesticide leaching and runoff (Polanco Rodríguez et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%